Analisis Pengaruh Paket Kebijakan Ekonomi XVI terhadap Peningkatan Investasi di Indonesia Tahun 2019 - Paulus, Hosea Stefan; Erawan, I Ketut Putra; Mahaswari Jayanthi Mertha, A.A Sagung Mirah (Jurnal Nawala Politika, 2021)
ABSTRACT The aim of this research is to determine the effect of Paket Kebijakan Ekonomi XVI to increasing investment in Indonesia. The method of this research is qualitative. The data were collected from literature studies, some statistical data which taken from The Badan Koordinasi Penanaman Modal (BKPM) and any online media resources. This research, the data is presented in tables, graphs, and also charts then narrated narratively. The results showed that the Paket Kebijakan Ekonomi XVI was a policy issued by the government (November, 2018) to attract investors for come to Indonesia. This policy consists of three important points, namely: tax holiday, the negative list of investment and export proceeds. This research reveals the implementation of this policy has an influence in increasing investment, where this policy provide incentives for the climate investment. Keywords : Investment, Paket Kebijakan Ekonomi XVI, Incentives